1995
DOI: 10.1002/eji.1830251004
|View full text |Cite
|
Sign up to set email alerts
|

A B7‐1‐transfected human melanoma line stimulates proliferation and cytotoxicity of autologous and allogeneic lymphocytes

Abstract: B7 co-stimulation is necessary to activate resting T cells upon antigen recognition by the T cell receptor. To see whether expression of B7 may render human melanoma cells able to stimulate T cells, a cloned melanoma line (Me1B6), which did not express B7-1, was transfected with the human B7-1 gene. In proliferation assays, B7-1 transfected cells (Me1B6/B7) showed greater stimulatory activity of allogeneic and autologous peripheral blood lymphocytes (PBL) compared to parental, non-transfected tumor cells. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…Isolation and in vitro characterization of IFN-producing human melanoma cell lines The human melanoma cell lines 8863 (metastatic melanoma) 20 and 1B6 (primary melanoma) 21 were infected with the recombinant retroviruses LXSN and LCIFNSN, derived from the retroviral vectors schematically depicted in Figure 1. Following selection into G418-containing medium, cell lines producing approximately 1000 IU/ml of IFN were isolated from both 8863 and 1B6 cells (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolation and in vitro characterization of IFN-producing human melanoma cell lines The human melanoma cell lines 8863 (metastatic melanoma) 20 and 1B6 (primary melanoma) 21 were infected with the recombinant retroviruses LXSN and LCIFNSN, derived from the retroviral vectors schematically depicted in Figure 1. Following selection into G418-containing medium, cell lines producing approximately 1000 IU/ml of IFN were isolated from both 8863 and 1B6 cells (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…20 The HLA haplotype of the two patients, previously identified, was: patient 10538: HLA-A2, -A28, -B27, -B45, -C-, -C-, -DR7; patient 8863: HLA-A2, -A1, -B8, -B35, -Cw4, -C-, -DR3, -DR11. 20 The 1B6 and 8863 cell lines had been previously shown not to express the B7.1 co-stimulatory molecule. 20 Both cell lines were cultivated in RPMI-1640 supplemented with 50 u/ml penicillin, 50 g/ml streptomycin (BioWhittaker, Verviers, Belgium), and 10% FCS (Sebam, Berlin, Germany).…”
Section: Cell Linesmentioning
confidence: 93%
See 2 more Smart Citations
“…These vectors may be suitable for modification of tumour cells without extended culture ex vivo as Jaffee et al 25 reported high efficiency retroviral gene transfer into a number of primary human tumour explants without drug selection. Sule-Suso et al 26 …”
Section: Discussionmentioning
confidence: 99%